Strain-induced topological phase transition at (111) SrTiO_{3}-based heterostructures - M. Trama; V. Cataudella; C. A. Perroni (Physical Review Research, 2021)
The quasi-two-dimensional electronic gas at the (111) SrTiO_{3}-based heterostructure interfaces is described by a multiband tight-binding model providing electronic bands in agreement at low energies with photoemission experiments. We analyze both the roles of the spin-orbit coupling and of the trigonal crystal-field effects. We point out the presence of a regime with sizable strain where the band structure exhibits a Dirac cone whose features are consistent with ab initio approaches. The combined effect of spin-orbit coupling and trigonal strain gives rise to nontrivial spin and orbital angular momenta patterns in the Brillouin zone and to quantum spin Hall effect by opening a gap at the Dirac cone. The system can switch from a conducting to a topological insulating state via modification of trigonal strain within a parameter range which is estimated to be experimentally achievable.